Equilibrium mortgage choice and housing tenure decisions with refinancing - Matthew S. Chambers; Carlos Garriga; Don Schlagenhauf (Federal Reserve Bank of Atlanta, 2007)
The last decade has brought about substantial mortgage innovation and increased refinancing. The objective of this paper is to understand the determinants and implications of mortgage choice in the context of a general equilibrium model with incomplete markets. The equilibrium characterization allows us to study the impact of mortgage financing decisions in the productive economy. We show the influence of different contract characteristics such as the down payment requirement, repayment structure, and the amortization schedule for mortgage choice. We find that loan products that allow for low or no down payment or an increasing repayment schedule increase the participation of young and lower-income households. We find evidence that the volume of housing transactions increases when the payment profile is increasing and households have little housing equity. In contrast, we show that loans that allow for a rapid accumulation of home equity can still have positive participation effects without increasing the volatility of the housing market. The model predicts that the expansion of mortgage contracts and refinancing improves risk sharing opportunities for homeowners, but the magnitude varies with each contract.
Keywords: E0; D58; D91; R21; 330; macroeconomics; housing; mortgages; Hypothek; Immobilienfinanzierung; Konditionen; USA